Protection of young children from influenza through universal vaccination - Principi, Nicola (Hum Vaccin Immunother, 2015)
Influenza is a very common disease among infants and young children, with a considerable clinical and socioeconomic impact. A significant number of health authorities presently recommend universal influenza vaccination for the pediatric population, but a large number of European health authorities is still reluctant to include influenza vaccination in their national vaccination programs. The reasons for this reluctance include the fact that the protection offered by the currently available vaccines is considered poor. This review shows that although future research could lead to an increase in the immunogenicity and potential efficacy of influenza vaccines, the available vaccines, even with their limits, assure sufficient protection in most subjects aged ≥ 6 months, thus reducing the total burden of influenza in young children and justifying the recommendation for the universal vaccination of the whole pediatric population. For younger subjects, the vaccination of their mother during pregnancy represents an efficacious strategy.